TINJAUAN DAKTILITAS LENTUR DINDING BATA MERAH DENGAN STRAPPING BAND ARAH RETAK VERTIKAL (Studi Kasus: Dinding Plesteran 1 cm dengan Beban Siklik Quasistatik) - , FREDERICA NEO, Dr. -Ing. Ir. Andreas Triwiyono ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Brick masonry wall is usually used as chamber partition in Indonesia. As Indonesia is in earthquake-prone area, those brick masonry walls need to be strengthened so that it wouldnât harm livings. One of the applicable, easy to be found and cheap wall strengthening method is by using strapping-band meshes. This research is expected to support previous strapping band researches, with a better approach to earthquake load by applying cyclic quasistatic flexural load in out-of plane direction of walls. Wall specimens were made in 4 variations: without strapping, with strapping interval of 20 cm, 15 cm and 10 cm. Every wall was given strapping band mesh and 1 cm plastering at both sides, with cement-sand ratio of 1 : 6. Reversed cyclic load was applied to all of the walls in 12 cycles to reach mid-span deflection of: 0,13 mm